The effect of sunburn damage on the fruit quality parameters of apple (Malus domestica cv. Idared) - Budai, Lejla; Racskó, József; Szabó, Zoltán; Soltész, Miklós; Farkas, Ervin; Thurzó, Sándor; Drén, Gábor; Nagy, János; Dani, Mária; Nyéki, József (Acta Agraria Debreceniensis, 2005)
In the present study the authors investigated the effect of sunburn injury on fruit quality parameters (cover colour, depth of tissue damage, fruit flesh firmness, dry matter content) of apple. The symptoms of sunburn injury appeared as concentric rings, differing in colour from each other and the cover colour. This can be connected with the ratio of the injury. The authors observed the following colours on the fruit surface (from the epicentre of spots on the surface of the fruit) dark brown (strongly damaged), light brown (moderately damaged), pale red transition (weakly damaged), red surface cover colour (not damaged). Sunburn of apple fruits is a surface injury caused by solar radiation, heat and low relative humidity. In the initial phase, a light corky layer, golden or bronze discolouration and injuries of the epidermal tissue appear on the surface exposed to radiation. Thus, it detracts from the fruit’s appearance, but in most of the cases it would not cause serious damages in the epidermal tissue. The depth of tissue damage is not considerable, its values are between 1.5-2.0 mm in general. It is commonly known, that tissue structure of the apple fruit is not homogeneous. Accordingly, the degree of injury shows some differences under the different parts of the fruit surface. On the basis of the flesh firmness studies, it can be stated that the flesh firmness of the damaged parts increases due to the sunburn effect. This is due to the fact that the damaged plant cells die, the water content of the tissue decreases and it hardens. However, due to this reduction in the water content the dry matter content will increase.